PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN GILIRENG KABUPATEN WAJO - ., Maryam (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The goal to be achieved in this research is to know and analyze the influence of leadership style on employee performance. and to know and analyze the influence of leadership style on employee performance. The population in this study is the employees of the District Office Gilireng Wajo Regency amounting to 42 people. In the sample study, the authors used questionnaires from the population is all employees of District office Gilireng Wajo Regency amounting to 42 people. This study was conducted on the entire population, because the number of employees in the office is relatively small in number of as many as 42 employees. Based on the results of research shows leadership style has a significant influence on employee performance and gives a low effect on employee performance. Leadership style effect on employee performance At Gilireng District Office. That is, that to achieve more effective employee performance based on organizational goals and expectations then the leadership must pay attention to a good leadership style in order to improve skills and technical skills based on the function and task of an employee.